SOCIO-PSYCHOLOGICAL MECHANISMS OF FORMING SUPPORT FOR POLITICAL LEADERSHIP IN UKRAINE - Aleshchenko, Viktor; Dziuba, Oksana; Kokarcha, Yuliia (Personality and environmental issues, 2026)
The article presents a socio-psychological analysis of the formation of support for political leadership in contemporary Ukrainian society. Political leadership is conceptualized not as a formal managerial position or an institutionally fixed status, but as a psychological process of influence realized through interaction between the leader and social and political communities. This approach makes it possible to focus on internal psychological processes through which support for a political leader emerges, stabilizes, and transforms under conditions of social instability, crisis challenges, and the digitalization of political communication.The purpose of the article is to identify and analyze the key socio-psychological mechanisms underlying the formation of support for political leadership in the contemporary Ukrainian social space. The methodological framework of the study is based on a theoretical-analytical and systemic approach integrating concepts from social and political psychology. Within this framework, political leadership is interpreted as a form of group interaction shaped by processes of social identification, trust, emotional influence, communicative construction of meanings, and the personalization of political processes.The scientific novelty of the article lies in a systemic interpretation of these socio-psychological mechanisms as an interconnected whole that ensures the formation, consolidation, and stabilization of support for a political leader. Unlike fragmentary approaches that focus on isolated psychological factors, the article substantiates that the effectiveness of leadership influence is determined by the combined action of identification, trust-based, emotional, and communicative processes within group consciousness.It is concluded that under conditions of crisis challenges and digital environments, support for political leadership increasingly acquires a psychological and compensatory function aimed at reducing social tension and restoring a sense of stability. The socio-psychological perspective provides a deeper understanding of the dynamics, possibilities, and limits of political leadership in contemporary Ukrainian society and creates a theoretical basis for further empirical research in the field of political psychology.